KAJIAN KARAKTERISTIK DAN KETERKAITAN SPASIAL PERDAGANGAN MOBIL OTO BURSA TVRI JOGJA DESA SINDUADI KECAMATAN MLATI KABUPATEN SLEMAN YOGYAKARTA - , SUCIYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
TVRI Yogyakartaâs Automobile Markets activity has been held since 2002. Every Saturday and Sunday, hundreds of secondhand cars with a variety of brands, types, and years of production always packed on the TVRI Yogyakarta area. The purposes of this research are to: (1) Knowing the characteristics of sellers and buyers at TVRI Yogyakartaâs Automobile Market. (2) Knowing TVRI Yogyakartaâs Automobile Marketâs spatial linkage. (3) Knowing TVRI Yogyakartaâs Automobile Marketâs policy implications. The research method used is the quantitative research method with primary and secondary data analysis. Techniques used in sampling is quota sampling technique. The analysis technique used are the analysis of cross-tabulation, spatial analysis and descriptive analysis. The results of this research indicates that the sellerâs characteristics are the majority of the class workforces belongs to the car dealers, civil servants and private employees while students isnât belong to the class workforces. The buyerâs characteristics are the majority of unmarried buyers choses hatchback and sedan while the majority of married buyers chose MPV (family car). The majority of buyers choose a car with a price class between Rp.101-150 million. TVRI Yogyakarta Automobile Marketâs operating hours is at 08:00 am to 05:00 pm, block spatial planning system is not determined by the car types, but only serves to facilitate the committee / manager while the payment system can be done via Bank BRI, berniaga.com and Sinarmas. TVRI Yogyakartaâs Automobile Market create spatial linkage between a region with other regions, due to both the seller and the buyer does not just come from the Yogyakarta but comes from outside Yogyakarta too, such as from Central Java, Banten, East Java, West Java, and Jakarta. The policy implications of TVRI Yogyakartaâs Automobile Market is TVRI Yogyakartaâs Automobile Market need to be maintained because TVRI Yogyakartaâs Automobile Market provide multiplier effect for commerce, it can also provide employment and contribute to the economy in the province.